The Sirius Passet Lagerstätte of North Greenland—A geochemical window on early Cambrian low-oxygen environments and ecosystems - Hammarlund, E; Smith, M; Rasmussen, J; Nielsen, A; Canfield, D; Harper, D (Wiley, 2018)
The early Cambrian Sirius Passet fauna of northernmost Greenland (Cambrian Series 2, Stage 3) contains exceptionally preserved soft tissues that provide an important window to early animal evolution, while the surrounding sediment holds critical data on the palaeodepositional water-column chemistry. The present study combines pal-aeontological data with a multiproxy geochemical approach based on samples col-lected in situ at high stratigraphic resolution from Sirius Passet. After careful consideration of chemical alterations during burial, our results demonstrate that fos-sil preservation and biodiversity show significant correlation with iron enrichments (FeHR/FeT), trace metal behaviour (V/Al), and changes in nitrogen cycling (δ15N). These data, together with Mo/Al and the preservation of organic carbon (TOC), are consist-ent with a water column that was transiently low in oxygen concentration, or even intermittently anoxic. When compared with the biogeochemical characteristics of modern oxygen minimum zones (OMZs), geochemical and palaeontological data col-lectively suggest that oxygen concentrations as low as 0.2–0.4 ml/L restricted bio-turbation but not the development of a largely nektobenthic community of predators and scavengers. We envisage for the Sirius Passet biota a depositional setting where anoxic water column conditions developed and passed over the depositional site, possibly in association with sea- level change, and where this early Cambrian biota was established in conditions with very low oxygen.